Economic Impact of Illness with Health Insurance but without Income Insurance - Sven Neelsen; Supon Limwattananon; Owen O'Donnell; Eddy van Doorslaer (Tinbergen Institute, 2015)
We examine economic vulnerability to illness when, as for informal sector workers in Thailand, there is universal coverage for health care but earnings losses are uninsured. Even with comprehensive health care entitlement, severe illness that strikes an initially healthy worker is found to raise out-of-pocket medical expenses by around two thirds and increase the probability that medical spending absorbs more than a tenth of the household budget by nine percentage points. Moreover, severe illness reduces the probability of remaining in employment by 18 points and precipitates a reduction in household labor income of almost one third. Despite the rise in medical expenses and fall in earnings, households are able to maintain expenditure on goods and services other than medical care by drawing on remittances and informal transfers, cutting back on saving, and by borrowing. In the short term, informal insurance fills gaps left uncovered by formal insurance but there is likely to be subst antial exposure to economic risks associated with long-term illness.
Keywords: I13; J46; O12; 330; Health; medical expenditure; social insurance; universal coverage; Thailand